Multi-objective pose optimal distribution method for the feed support system of Five-hundred-meter Aperture Spherical radio Telescope. (6th February 2018) - Deng, Sai; Jing, Fengshui; Zheng, Rongzhang; Liang, Zize; Yang, Guodong
The Five-hundred-meter Aperture Spherical radio Telescope is the world's largest single-dish radio telescope and is located in the southwest of China. The cable-driven parallel robot and A-B rotator of the feed support system in Five-hundred-meter Aperture Spherical radio Telescope are designed to realize the theoretical position and attitude of the receiver. The feed support system is a pose-redundant and rigid–flexible coupling system; thus, the method of pose distribution between the A-B rotator and the cable-driven parallel robot impacts on the cable tension distribution and stiffness of the feed support system, which are crucial to the feed support system stability. The main purpose of this study is to examine the pose optimal distribution method for the feed support system. First, a mechanical model of the feed support system, which considers the time-varying barycenter of the feed cabin and the back-illuminated strategy of the receiver, is established. Then, a pose distribution method that ensures the position and attitude accuracy of the receiver is proposed for the feed support system. Considering the performance indices of the variance of cable tensions and the stiffness of the cable-driven parallel robot, an optimization of the rotation angles of the A-B rotator with multiple objectives is implemented using a genetic algorithm. Finally, simulations are conducted to demonstrate the effectiveness of the proposed method compared with others. Results show that the proposed approach not only ensures the attitude accuracy of the receiver but also maintains the lower variance of cable tensions and higher stiffness of the feed support system.